Susceptibility of Plutella xylostella to Heterorhabditis sp. SL0708 (Rhabditida: Heterorhabditidae) - SÁENZ-A., ADRIANA (Revista Colombiana de Entomología, 2012)
Plutella xylostella (Lepidoptera: Plutellidae) known as the diamondback moth (DBM) is the more important pestof cruciferous crops in Colombia. The most common control strategy has been the use of chemically synthesized insecticides such as pyrethroids, carbamates, organophosphates and growth regulators. As an alternative control, we evaluated the susceptibility of third instar DDM to Heterorhabditis sp. SL0708 under laboratory conditions. We tested five doses of infective juveniles IJ (0, 100, 300, 600.1200 IJ/ml/5 larvae) and every 24 hours we assessed symptoms of mortality and recovery IJ. Larvae affected by Heterorhabditis sp. SL0708 showed color changes from green to brown, little mobility and a flabby body. Some larvae reached the pupa instar and even reached first generation adults. The average mortality rate was 95.6%, with a time of death between 48 and 72 hours. There were significant differences at a dose of 100 IJ. Around 2,743 IJ were recovered per larvae daily average along 5 days. The larvae of P. xylostella were susceptible to Heterorhabditis sp.SL0708 IJ, indicating that its pathogenicity should be evaluated in greenhouse and field conditions.